PENGARUH PERSEPSI MANFAAT, KEMUDAHAN PENGGUNAAN, DAN KEPERCAYAAN TERHADAP SIKAP PENGGUNAAN LAYANAN INTERNET BANKING (Studi komparasi Pada Nasabah Pengguna Internet Banking Bank Mandiri Semarang Berdasarkan Tingkat Pendapatan) - Mirzha Rusfianto; Widiartanto Widiartanto; Bulan Prabwani (Universitas Diponegoro, 2016)
This research is motivated by the rapid development of information technology that it need quick banking transactions to help activities of customers' banking transactions. Internet Banking is one of the types of services offered by the Bank. The purpose of this study was to determine the effect of variables perceived usefulness, ease of use and trust in the attitude of the use of Internet Banking Mandiri. population is user of Internet Banking service. sample of 50 respondents for each level of income with sampling use accidental sampling technique. Analysis of the data used in this study using SPSS 18.0, which carried out a comparison between the validity, reliability, correlation coefficient, coefficient of determination, simple and multiple regression analysis and significance test (t test and F). The results of this study indicate that the perceived usefulness, ease of use and trust to have an influence on the attitude of the use of Mandiri Internet Banking Suggestions can be delivered is preferably enhanced website security and maintenance, thereby reducing the level of Flaws login and reduce the level of cyber crime.